STRATEGI KOMUNIKASI PESANTREN DALAM MENYEBARKAN NILAI-NILAI ISLAM MELALUI MEDIA DIGITAL - Hotna Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the communication strategies used by Islamic boarding schools in spreading Islamic values ​​through digital media, motivated by the rapid development of digital technology that opens up new opportunities for Islamic boarding schools in spreading Islamic teachings to the wider community, using qualitative research methods with a case study approach where data is collected through in-depth interviews, observations, and document analysis, the results of the study show that Islamic boarding schools use various digital communication strategies such as the use of social media, websites, and mobile applications to convey religious messages effectively and integrate Islamic values ​​in the digital content presented so that it can attract the interest of the community, especially the younger generation, the conclusion of this study is that the use of digital media by Islamic boarding schools has great potential to increase the spread of Islamic values ​​more widely and effectively so that it is important for Islamic boarding schools to continue to develop and optimize relevant and innovative digital communication strategies.